(untitled) (INNOVATIVE ECONOMY, 2021)
Palchuk O.V., Gai O.M. ACCOUNTING POLICY AND ITS ROLE IN THE FORMATION OF INFORMATION SUPPORT OF INNOVATION ACTIVITY MANAGEMENT Purpose. Research of features of innovative activity and its accounting reflection; determining their impact on the formation of accounting policies in order to build an effective accounting and information system of innovative activity management of the enterprise. Methodology of research. Realization of the purpose was carried out by means of the epistemological method which gave the chance to specify the essence of accounting policy on various directions of the innovation process; system-structural method, which allowed to classify the objects of innovation activity and its accounting. General scientific methods (induction, deduction, analysis, synthesis, abstraction, generalization) were used to develop the concept of accounting and information support for innovation activity management. Findings. It is established that the special complexity and diversity of innovation is the reason for the existence of diversity and determines the relevance of accounting policies in the formation of information support for innovation activity management. The main stages of the procedure of formation of accounting and information support of innovation activity management are proposed and the role of accounting policy, in this case, is clarified. Based on the analysis of the peculiarities of innovation, the requirements for the accounting system are formed, which should be taken into account when forming the accounting policy in order to form the information resource of innovation activity. Originality. The place of accounting policy in the process of formation of information resources of innovation activity is substantiated. The content, stages, and features of the formation of accounting policy taking into account the specifics of innovation activity are described. A distinctive feature of the proposed approach is the construction of accounting and information support for innovation activity management, taking into account the classification of objects of innovation in three areas: financing of innovation; creation (acquisition) of an innovative product; commercialization of innovation activity results. This approach will help streamline accounting methods and improve reporting transparency. Practical value. Determining the features of accounting support and accounting policy of innovation allows forming models of accounting reflection of innovation processes in accounting accounts, to determine algorithms for forming financial reporting indicators, and methods of internal accounting for their use in innovation management, taking into account industry specifics, business specifics and innovation activities of specific enterprises. Key words: innovation activity, objects of innovation activity, information support, information resources, objects of accounting of innovation activity, accounting policy.